Study on Reduction Behaviour of Oxidized Mercury to Elemental Mercury through Lab-Scale Wet Simulator - Wu, Chengli; Wu, Jianxia; Cao, Yan; Li, Hanxu; Pan, Weiping (Asian Journal of Chemistry, 2014)
The re-emission of elemental mercury was simulated in the lab-scale wet scrubber. Absorbing and dissolving of vapour Hg2+ were simulated in the slurry as HgCl2 standard solution was continuously injected into the slurry. Some factors such as oxidation models of wet flue gas desulphurization system, ratio of oxygen to sulphur and a trimercapto-s-trazine trisodium salt additive on elemental mercury re-emissions were investigated. Trends of oxidation-reduction potential and pH values of testing slurries with different SO2 concentrations and testing time were studied. Elemental mercury re-emissions occurred in reduction atmosphere when oxidation-reduction potential of the slurries were negative.